2020
DOI: 10.1136/bmjsem-2019-000711
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and psychological well-being among professional rugby league players from the UK

Abstract: ObjectiveThis study aimed to measure depressive symptoms, anxiety symptoms and psychological well-being among a sample of Super League players, the highest tier of professional rugby league in the northern hemisphere.MethodsBetween November 2018 and July 2019, a sample of 233 Super League players completed questionnaires that assessed depressive symptoms, anxiety symptoms and psychological well-being.ResultsPlayers exhibited normal (85.8%), mild (11.6%) or moderate/severe (2.6%) depressive symptoms. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Mental Health in Danish Youth Soccer Players the time). Scores ≤23 indicate below average well-being, scores from 24 to 29 indicate average well-being, and scores ≥30 indicate above average well-being (Nicholls, Madigan, Fairs, & Bailey, 2020). The Cronbach α in this study was a satisfactory .81.…”
Section: Methodsmentioning
confidence: 50%
See 1 more Smart Citation
“…Mental Health in Danish Youth Soccer Players the time). Scores ≤23 indicate below average well-being, scores from 24 to 29 indicate average well-being, and scores ≥30 indicate above average well-being (Nicholls, Madigan, Fairs, & Bailey, 2020). The Cronbach α in this study was a satisfactory .81.…”
Section: Methodsmentioning
confidence: 50%
“…The average well-being scores of female soccer players (M = 25.07) are higher than the average of females in the Danish general population (M = 24.10), and the same was noted for male players (M = 27.15) whose average scores are higher than those of general population peers in their age group 16-25 (M = 25.80) years. Compared with U.K. male rugby players (M = 25.07; Nicholls et al, 2020), the Danish male soccer Mental Health in Danish Youth Soccer Players players expressed elevated well-being. Our data show that female soccer players generally express a higher stress level compared with their male counterparts.…”
Section: Discussionmentioning
confidence: 78%
“…In a previous study using samples similar to this current study, Nicholls et al examined the prevalence and degree of anxiety and depression symptoms in UK professional rugby players [18], and they reported that 18.9% of athletes had mild and 13.7% had moderate/severe symptoms of anxiety. They also reported that the players showed mild (11.6%) and moderate/severe (2.6%) symptoms of depression [18].…”
Section: Introductionmentioning
confidence: 69%
“…World Rugby has documented the heavy load on physical and mental health associated with participating in competitive environments, and suggested that further research is needed to develop effective mental health support measures [ 8 ]. Professional rugby league players from the United Kingdom (UK) have exhibited mild (11.6%) or moderate/severe (2.6%) depressive symptoms, and likewise mild (18.9%) or moderate/severe (13.7%) anxiety symptoms [ 9 ]. We have reported comparable prevalence rates among Japan Rugby Top League players [ 10 ].…”
Section: Introductionmentioning
confidence: 99%